DEVELOPMENT OF COGNITIVE ASSESSMENT INSTRUMENTS ON BUFFER SOLUTION MATERIAL BASED ON HOTS (HIGHER ORDER THINKING SKILLS) - solikhin, febrian; Nurmiana Suswanti; Sura Menda Ginting (Universitas Negeri Surabaya, 2024)
The goal of this study is to construct a valid and reliable HOTS-based cognitive assessment tool. The HOTS-based assessment instrument was used to measure students' higher order thinking skills on the buffer solution material. The stages of this research were the analysis, design, development, implementation, and evaluation phases of the ADDIE model. The research subjects were students of class XI MIPA 4 at Senior High School 5 Bengkulu City during the 2021–2022 academic year. The research data came from expert validation sheets, needs analysis questionnaires, empirical test analysis, and examination of students' HOTS skills. The 20 multiple-choice questions and 10 essay questions made up the instrumen's features. The following are the outcomes: (1) The expert's assessment of the practicality of the material led to the creation of 26 valid questions, including 18 multiple-choice questions and 8 essays. (2) The empirical validity study produced 23 valid items, including 6 essay questions and 17 multiple-choice questions. (3) The reliability analysis results for both essays and multiple choice questions fell into the very good category, with scores of 0.94 and 0.98. (4) The findings of the examination of students' higher-order thinking skills revealed that 1 student was in the very good category, 5 students were in the good category, 5 students were in the fairly good category, 22 students were in the poor category, and 1 student was in the very poor category.